2012
DOI: 10.1371/journal.pone.0041837
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Influenza (A/H1N1) Vaccine Uptake among French Private General Practitioners: A Cross Sectional Study in 2010

Abstract: BackgroundIn July, 2009, French health authorities, like those in many other countries, decided to embark on a mass vaccination campaign against the pandemic A(H1N1) influenza. Private general practitioners (GPs) were not involved in this campaign. We studied GPs’ pandemic vaccine (pvaccine) uptake, quantified the relative contribution of its potential explanatory factors and studied whether their own vaccination choice was correlated with their recommendations to patients about pvaccination.Methodology/Princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…29 Improving understanding of these physicians' KABB toward their own vaccination and the factors determining it is essential because they not only act as role models for their patients, but because their behaviors for themselves can be determinant in their recommendations to their patients. This has been shown in the case of vaccination against influenza (positive association between their own and their patients' vaccination against seasonal influenza, 20 personal acceptance of vaccination against pandemic influenza predictive of GP/FPs' recommendation of this vaccine to their patients 22 ), but also, for example, for prescription of psychotherapy (GP/FPs who have undergone psychotherapy are more likely to recommend it 53 ) or help in quitting were not aware of them and 10% were not sure if they were aware of any recommendation -Potential barriers to vaccination: 10% reported that this vaccination would not benefit them because they do not get the flu, having to pay for the vaccine was a barrier for 30% of them 2006, Semaille et al…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…29 Improving understanding of these physicians' KABB toward their own vaccination and the factors determining it is essential because they not only act as role models for their patients, but because their behaviors for themselves can be determinant in their recommendations to their patients. This has been shown in the case of vaccination against influenza (positive association between their own and their patients' vaccination against seasonal influenza, 20 personal acceptance of vaccination against pandemic influenza predictive of GP/FPs' recommendation of this vaccine to their patients 22 ), but also, for example, for prescription of psychotherapy (GP/FPs who have undergone psychotherapy are more likely to recommend it 53 ) or help in quitting were not aware of them and 10% were not sure if they were aware of any recommendation -Potential barriers to vaccination: 10% reported that this vaccination would not benefit them because they do not get the flu, having to pay for the vaccine was a barrier for 30% of them 2006, Semaille et al…”
Section: Discussionmentioning
confidence: 91%
“…[17][18][19][20][21] Moreover, their recommendations to patients about vaccinations are associated with their vaccination behaviors and attitudes for themselves. [22][23][24][25][26] Their own vaccination might be important as a proxy for their potential "vaccine hesitancy," -a term that describes vaccination reluctance and was first studied in the general population 27,28 and, more recently, also among GP/FPs. 28,29 For all these reasons, identifying factors associated with their own vaccinations is important for improving vaccination coverage rates in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The survey described was the third of a series nested in the national panel of French GPs, designed to collect data regularly about their activity and practices. Its methodology has been presented elsewhere [17]. Briefly, 5170 GPs were randomly selected from the Ministry of Health's exhaustive database of health professionals in France.…”
Section: Methodsmentioning
confidence: 99%
“…The GPs who refused to take part did not differ from participants according to practice location, but were more frequently male (p = 0.02), older (p<10 −3 ), and had a higher workload in 2008 (p<10 −3 ). Lack of time (46.2%) and lack of interest in the panel (15.6%) were the reasons given most frequently for refusal [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation